Analisis penerapan penyesuaian tarif pajak penghasilan badan dan prosedur pemindahbukuan - Sagita, Melda; Sugiyanto, Sugiyanto; Sumaryana, Fitriana Dewi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Taxpayers often make mistakes in determining the tax burden that causes losses for the taxpayer. The purpose of this study is to determine the appropriate and beneficial tax provisions for cooperative business entities in determining the income tax payable. The data obtained is sourced from the Cooperative PHU Report for the Financial Years of 2020 and 2021. The analytical method used is descriptive qualitative analysis. The results of the study concluded that Cooperatives benefited more from using the Tariff of Government Regulation in Lieu of Law no. 1 of 2020, because the tax burden owed by the taxpayer is smaller than the calculation according to the Tariff Regulation Article 17 paragraph 2 letter a of Law no. 36 of 2008, with the results of the discussion and analysis, namely the Koperasi Serba Usaha Tandangsari, so far, in compliance with the cooperative, it has carried out the obligation to pay taxes. The Koperasi Serba Usaha Tandangsari should be able to adjust the applicable corporate income tax rate.